An integrated analysis of the chairman's letter and firm performance - Leite, Carolina Simões Correia Vieira (2021)
The impact of the use of complex financial narratives was studied and its link with firm performance. This was done by analysing one of the most important sections of the annual report, the chairman letter. The use of complex financial narratives was measured by the three variables: Fog Index, Flesch Formula and Log(Word Count). These three variables were regressed and analysed against two measures of financial performance (EPS and ROA) and a series of control variables, using a multivariate model. Furthermore, we also studied the use of forward looking words, during periods of economic struggle. Following this analysis our results confirm that non-financial English firms include several complex financial narratives within their chairman letter whenever firm performance declines. In addition, we found a negative relationship between the use of forward-looking words during periods of financial struggle.